2014
DOI: 10.1016/j.appet.2014.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Who reports noticing and using calorie information posted on fast food restaurant menus?

Abstract: Objectives Identify consumer characteristics that predict seeing and using calorie information on fast food menu boards. Methods Two separate data collection methods were used in Philadelphia during June 2010, several weeks after calorie labeling legislation went into effect: 1) point-of-purchase survey and receipt collection conducted outside fast food restaurants (N=669) and 2) a random digit dial telephone survey (N=702). Logistic regressions were used to predict the odds of reporting seeing, and of repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 14 publications
(22 reference statements)
4
37
3
Order By: Relevance
“…Unlike the studies by Breck et al 39 and Green et al ,38 college degree was not a determinant of menu label use in this study. Breck et al 39 also reported that the odds of seeing and using the menu labels were higher among females, obese individuals, those concerned about weight gain, and those eating out in fast food restaurants at least five times a week. Schindler et al 40 found that barriers to the use of menu labels included price, food preferences and hunger.…”
Section: Discussioncontrasting
confidence: 90%
“…Unlike the studies by Breck et al 39 and Green et al ,38 college degree was not a determinant of menu label use in this study. Breck et al 39 also reported that the odds of seeing and using the menu labels were higher among females, obese individuals, those concerned about weight gain, and those eating out in fast food restaurants at least five times a week. Schindler et al 40 found that barriers to the use of menu labels included price, food preferences and hunger.…”
Section: Discussioncontrasting
confidence: 90%
“…4, 5, 9 They are important because they do not rely on the customer to first notice and then be influenced by the menu label to make a healthy choice. Relatively few restaurant customers notice menu labels, 14,15 and when they do, the evidence of the degree to which they influence food choices is mixed. 1418 Restaurants with a specific menu focus (e.g., burgers) may be less likely to change existing core menu items but more likely to introduce new non-core menu items.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few restaurant customers notice menu labels, 14,15 and when they do, the evidence of the degree to which they influence food choices is mixed. 1418 Restaurants with a specific menu focus (e.g., burgers) may be less likely to change existing core menu items but more likely to introduce new non-core menu items. 19, 20 …”
Section: Introductionmentioning
confidence: 99%
“…This medium offers, however, only limited space, and nutritional information is usually confined to calorific content and the presence of key allergens (Breck et al 2014). Another way to provide enhanced dish information is through a dedicated menu board located within the foodservice establishment (Conkin et al 2012), though consumers may feel overwhelmed with information.…”
Section: Literature Review: Health Consciousness and The Need For Infmentioning
confidence: 99%